Nutritional considerations of a paediatric gluten-free food guide for coeliac disease. Issue 3 (14th February 2022) - Mager, Diana R.; Cyrkot, Samantha; Lirette, Christine; Brill, Herbert; Dowhaniuk, Jenna; Mileski, Heather; Basualdo-Hammond, Carlota; Nasser, Roseann; Assor, Esther; Marcon, Margaret; Turner, Justine M.
Abstract: The gluten-free (GF) diet is the only treatment for coeliac disease (CD). While the GF diet can be nutritious, increased reliance on processed and packaged GF foods can result in higher fat/sugar and lower micronutrient intake in children with CD. Currently, there are no evidence-based nutrition guidelines that address the GF diet. The objective of this cross-sectional study was to describe the methodological considerations in forming a GF food guide for Canadian children and youth (4–18 years) with CD. Food guide development occurred in three phases: (1) evaluation of nutrient intake and dietary patterns of children on the GF diet, (2) pre-guide stakeholder consultations with 151 health care professionals and 383 community end users and (3) development of 1260 GF diet simulations that addressed cultural preferences and food traditions, diet patterns and diet quality. Stakeholder feedback identified nutrient intake and food literacy as important topics for guide content. Except for vitamin D, the diet simulations met 100 % macronutrient and micronutrient requirements for age–sex. The paediatric GF plate model recommends intake of >50 % fruits and vegetables (FV), <25 % grains and 25 % protein foods with a stronger emphasis on plant-based sources. Vitamin D-fortified fluid milk/unsweetened plant-based alternatives and other rich sources are important to optimise vitamin D intake. The GF food guide can help children consume a nutritiously adequate GF diet and inform policy makers regarding the need for nutrition guidelines in paediatric CD.